Optimization of Making Dahsukim Permits for Foreign Employees Working on Lay Up Ships At PT. Trans Shipping Agency Batam - Paula Yuliarta Br Sitanggang; Syarifur Ridho; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of writing this paper is to find out and analyze how to optimize the making of Dahsuskim permits for the residence permits of foreign crew who will work on lay up ships at PT. Trans Shipping Agency Batam and foreign crew who are in Indonesian waters for a long time must be in Dahsuskim. The method used in collecting data is using the Field Research and Liberary Research methods. Dahsuskim is a limited stay permit for Special Immigration Facilities which is specifically intended for foreign workers who work on ships or floating equipment in Indonesian waters. The long processing process has had a significant impact on foreign workers and companies. In carrying out Lay Up activities, the Ship Owner appoints an agent or shipping company to manage all processes of Lay Up activities including taking care of the ship's needs and the needs of the ship's crew. In contrast to routine ships, Lay Up ships will stay for a long time in Indonesian waters and must have permits including residence permits for foreign crew entering and exiting Indonesia. In this case, crew or foreigners entering and exiting Indonesia must have a visa which can only be obtained by submitting an application to the office. Immigration/General of Indonesian Immigration. Immigration plays a very important role because immigration is a government agency whose activities include providing all Immigration permits in the form of visas, entry permits, registration of foreigners, re-entry permits (Exit Re-Entry Permit), non-return exit permits (Exit Permit Only).